The Impact of Multi-Level Governmental Policy on Employment and Educational Training Opportunities in Rural Catalonia - Agahi, Omeed; Pell-Dempere, Maria Isabel; Prieto-Flores, Òscar (Calitatea Vieții, 2023)
Despite numerous policy interventions to improve education and employment outcomes across the European Union in the last decade, youth unemployment rates continue to be elevated in many EU countries. As rural rates are among the highest, the rural−urban divide is receiving ever-increasing attention, and the various dimensions of rural youth unemployment are becoming increasingly prevalent in the discourses of education and employment across Europe, not least in Spain, one of the European countries with the most significant degree of rurality. The objective of this paper is to analyse the differences in Youth-based Active Labour Market policies between rural and urban areas in the Spanish region of Catalonia, using a mix of longitudinal data collection and analysis, along with an examination of the relevant policy framework at all levels of government. Our findings reveal key differences between urban and rural opportunities, and shed light on how multilevel governance may play a role in expanding or reducing these gaps.